Human capital advances in theory and evidence - Hartog, Joop; Maassen van den Brink, Henriëtte (Cambridge University Press, 2007)
At a time when governments and policy-makers put so much emphasis on 'the knowledge economy' and the economic value of education, human capital theory has never been more important. However, research in this area is often very technical and therefore not easily accessible to those who wish to use it as a guide to policy formation. This book provides an interface between such research and its potential applications in government, education and business. Reporting on a major research initiative, new findings are presented in a non-technical way on three major themes: measuring the benefits from human capital, applications of the human capital model, and policy interventions. Aimed at academic researchers and professionals concerned with the problems and techniques of human capital theory, it will also be useful for graduate courses on the economics of education to complement standard textbooks.